Labor market dynamics: a time-varying analysis - Zanetti, F; Mumtaz, H (University of Oxford, 2014)
This paper studies how key labor market stylized facts and the responses of labor market variables to technology shocks vary over the US postwar period. It uses a benchmark DSGE model enriched with labor market frictions and investment specific technological progress that enables a novel identification scheme based on sign restrictions on a SVAR with time-varying coefficients and stochastic volatility. Key findings are: i) the volatility in job finding and separation rates has declined over time, while their correlation varies across time; ii) the job finding rate plays an important role for unemployment, and the two series are strongly negatively correlated over the sample period; iii) the magnitude of the response of labor market variables to technology shocks varies across the sample period.